Pregnant mothers' strategies for the management of pregnancy concerns - Narjes Sadat Borghei; Ali Taghipour; Robab Latifnejad Roudsari (Tehran University of Medical Sciences, 2017)
Background & Aim: Mothers during pregnancy face many concerns. Identifying mothers' strategies to manage those concerns can help healthcare providers to promote their mental health. The aim of this study was to explore pregnant mothers' strategies for the management of their concerns during pregnancy. Methods & Materials: This qualitative study was conducted in Gorgan city during 2014-2015. The study participants were 20 pregnant women and three of their husbands as well as three experienced midwives who were selected using purposive sampling and interviewed through semi-structured interview. Data were analyzed through conventional content analysis using the MAXQDA software. Results: Data analysis led to the emergence of five main categories including the utilization of purposive knowledge acquisition, reliance on the leverage of spirituality, thinking management and stress control, the effort to maintain and improve familial interactions and emotional preparation for pregnancy. Conclusion: The five strategies used by pregnant women to manage their concerns, were identified in this study. Midwives can play an important role in implementing these strategies and empowering pregnant women.